The impact of online testimonials on job seekers' perceptions of organizational attractiveness - Castro, Maria Madalena de Almeida Ribeiro Anglin de (2017)
The world is constantly changing and the great challenge is to keep up with this evolution. We live in a world where boundaries are being extinguished and distances becoming shorter. To meet the new challenges of globalization, companies need tools that allow them to work faster, with agility and simplicity, in order to guarantee a competitive advantage in the labor market, always being essential the investment in their human capital. This study was conducted to identify the perspective of potential candidates regarding the attractiveness strategies adopted by companies, particularly the online testimonials. In a first moment a qualitative study was addressed to companies, with the aim of identifying which are their disclosure channels, the reasons that led them to adopt the strategy of online testimonials and how they managed their implementation, with a view to defining strategies to be applied in the future. It was also a goal of this study to evaluate how the corporate websites influence the image that potential candidates create about the company, to analyze the impact of online testimonials on the potential candidates' perceptions about the company, to study the degree of credibility associated with online testimonials and to understand how this tool contributes to the effectiveness of the message that the company wants to convey. From the results it is concluded that although companies are increasingly investing on this approach, potential applicants still show some reservations towards it, though not refusing its importance.